Surgical Treatment of Atrial Fibrillation and Flutter in Patients with Atrial Septal Defects - Oleksii A. Lozovyi; Kostiantyn V. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2024)
The article analyzes the results of surgical treatment of atrial fibrillation or flutter in patients with an atrial septal defect (ASD).The aim. To increase the effectiveness of surgical treatment of concomitant atrial fibrillation (AF) / atrial flutter (AFL) in patients with ASD.Materials and methods. The study included 124 people, with a mean age of 38.3 ± 4.4 years. The patients were divided into 3 groups. Group 1 included patients with ASD and concomitant AF/AFL who underwent closure of the ASD and radiofrequency ablation, while group 2 included patients with ASD and concomitant AF/AFL who underwent only closure of the ASD. The third group included patients over 18 years old with ASD without obvious AF/AFL who underwent ASD closure.Results. It was established that severity of the perioperative period after ASD plasty is due to the duration of the operation and the need for radiofrequency fragmentation of the atria. It was found that performing radiofrequency fragmentation of the atria leads to an increase in the time of artificial blood circulation and the time of artificial lung ventilation. The criteria for forming the research groups were the presence of arrhythmia and surgical tactics used to eliminate ASD. It was established that the duration of ASD plasty was significantly longer in patients from the 1st group (271.0 ± 43.1 min) compared to the corresponding indicator in patients from the 2nd group (211.0 ± 29.4 min) and of the 3rd group (191.3 ± 28.0 min) (p = 0.001, χ2= 18.02). The time of artificial blood circulation was also significantly longer in the 1st group (80.2 ± 13.0 min), compared to the corresponding indicator in the 2nd (45.0 ± 8.4 min) and 3rd groups (47.4 ± 7.3 min), which is caused by performing radiofrequency fragmentation of the atria (p = 0.001, χ2= 17.52).Conclusions. It was established that complexity of the treatment of ASD is due to the duration and traumatic nature of the operation and the need for radiofrequency fragmentation of the atria. It was found that performing radiofrequency fragmentation of the atria leads to an increase in the time of use of artificial blood circulation and, accordingly, reliably extends the time of the patient’s stay on artificial lung ventilation. At the same time, radiofrequency atrial fragmentation provides high clinical efficacy in eliminating AF/AFL.